Acute calcific tendinitis of the longus colli muscle masquerading as a retropharyngeal abscess: A case report and review of the literature. (2017) - Alamoudi, Uthman; Al-Sayed, Ahmed A.; AlSallumi, Yasser; Rigby, Matthew H.; Taylor, S. Mark; Hart, Robert D.; Trites, Jonathan R.B.
Highlights: The longus colli muscle is situated on the anterior surface of C1-C2 disk space. Calcific tendinitis of the longus colli muscle is a reactive self-limiting inflammatory response to the subacute deposition of calcium hydroxyapatite crystals on the tendon of the muscle. The clinical presentation is usually mistaken with other serious conditions, such as a retropharyngeal abscess, disk herniation, neck tumor or trauma. The importance of recognizing this pathology lies in preventing its misdiagnosis and mismanagement. This condition is usually managed conservatively with nonsteroidal anti-inflammatory drugs (NSAIDs). Abstract: Introduction: Acute calcific longus colli tendinitis, also known as retropharyngeal or acute calcific prevertebral tendinitis, is a reactive self-limiting inflammatory response to acute or subacute deposition of amorphous calcium hydroxyapatite crystals in the tendons of the longus colli muscle, anterior to the C1–C2 disk space. Case presentation: A 53-year-old man presented with a complaint of neck pain and odynophagia over a few days. Blood test findings showed mild leukocytosis and elevated C-reactive protein level. Computed tomography findings showed mild edematous prevertebral thickening involving the retropharyngeal space, predominantly on the left side, with no appreciable surrounding peripheral enhancement. A small amount of linear calcification/ossification involving the superior fibers of the left longus colli muscle, anterior to the C1 arch were also noted. Discussion: The patient's presentation could be easily misdiagnosed as a retropharyngeal abscess. However, the presence of subtle findings on CT would lead to the correct diagnosis. The management of this condition is mainly with nonsteroidal anti-inflammatory drugs. Conclusion: This study presents the characteristic radiological features of retropharyngeal calcific tendinitis. These features are subtle and could be missed. Once an accurate diagnosis is made, treatment with nonsteroidal anti-inflammatory drugs is indicated. The purpose of this case report is to highlight this rare condition's diagnosis and management.